A new X linked syndrome with mental retardation and craniofacial dysmorphism?. Issue 10 (October 1992) - Hyde-Forster, I; McCarthy, G; Berry, A C
Abstract : We present a syndrome manifested in two half brothers and their two maternal aunts which is characterised in the two boys by severe mental retardation and craniofacial dysmorphism (broad, coarse features and marked plagiocephaly with flattened occiput), and in the aunts merely by moderate mental retardation without dysmorphic features. The brothers do not seem to fall into any previously described X linked syndrome with mental retardation.